Cytomorphological Study of Hepatic Lesions by FNAC - Vyas, Jahnavi Nilay; Patel, Prashant R; Patel, Krutika; Bhagat, Vasudha M (Annals of Pathology and Laboratory Medicine, 2022)
Introduction: Fine Needle Aspiration Cytology (FNAC) is a simple, safe, very low-cost and rapid procedure for diagnostic purpose which makes surgical intervention and exploratory laparotomy unnecessary. The introduction of modern diagnostic imaging techniques, mainly ultrasonography (USG) and Computerized Tomography (CT), has enabled the detection and location of lesions in sites such as liver, which are not easily accessible to surgical biopsies. Aim: To assess the utility of FNAC in the diagnosis of liver lesions. To study the cytomorphological features, age and sex distribution of liver lesions. Materials and methods: The study included 24 liver lesions which were detected clinically or radiologically. USG guided FNA was done in all cases. The smears were stained with Haematoxylin and eosin (H and E), May Grunwald Giemsa (MGG) and Papanicolaou’s stains. A cyto-histopathological correlation was done wherever possible. From the residual material, additional slides and cell blocks were prepared. Special stains were used whenever required. In doubtful cases immunohistochemistry (IHC) was done on formalin-fixed paraffin cell blocks and immunocytochemistry on conventional smears wherever necessary and possible. Results: All the lesions were found to be malignant. Out of 24 liver FNA cases, maximum lesions were seen in females and the affected age group for liver malignancies was 51-60 years. Out of 24 liver FNA cases, 20 cases were metastatic and 4 were primary cases. Among metastatic cases, maximum cases were of metastatic adenocarcinoma and the primary lesions of liver included all cases of hepatocellular carcinoma. Conclusion: Fine needle aspiration cytology of liver is a simple, safe, repeatable and rapid diagnostic procedure. In case of hepatic lesions, it is of outmost advantage in recognizing the nature of lesion i.e., primary, and metastatic as well as in early diagnosis of lesion so that patient can be treated as early as possible.